UNIT 4.3 Mammalian Cell Culture. Issue 10 (1st May 2015) - Warner, Dennis R.; Sakai, Daisuke; Sandell, Lisa L.
Abstract : Mammalian cell culture is the process of growing animal cells in vitro in a flask or dish. This unit describes the methods, equipment, supplies, and reagents used in a cell culture laboratory. Because preventing contamination and maintaining purity of cell cultures is arguably the greatest challenge in animal cell culture, the principles of aseptic technique in mammalian cell culture are presented in detail. Cell culture media and additives are discussed. A method of counting cells and assessing their viability with a hemacytometer is illustrated. The steps needed to maintain an adherent cell line by feeding and passing cells from one culture vessel to another are presented, and variations for passing suspension‐grown cells are also outlined. Long‐term cryogenic storage of cells in liquid nitrogen is discussed and a protocol for freezing cells is provided, as are details for thawing and recovering viable cells from frozen stocks. © 2015 by John Wiley & Sons, Inc.